Experimental analysis and performance evaluation of a solar PV-driven diffusion absorption refrigeration system - Mohamed Rady; Mohanad Aljahdli; Abdullah Abuhabaya; Eydhah Almatrafi; Faisal Al Batati; Alaa Attar (Case Studies in Thermal Engineering)
This article presents a comprehensive analysis of the design, integration, and performance evaluation of a photovoltaic (PV) solar-driven aqua-ammonia diffusion absorption refrigeration (DAR) system. The present approach emphasizes a thorough indoor experimental phase to inform the design process and selection of the PV solar system for integration with the DAR unit. The experiments cover various start-up conditions, thermal power inputs to the generator, and evaporator loads, with temperatures measured at key points of the DAR unit. Steady-state results across a wide range of operating conditions are used to create performance maps and identify dynamic characteristics, crucial for estimating generator power for specific cooling loads. Outdoor experiments are conducted to evaluate the performance of the PV-driven DAR unit under typical hot climate conditions. The operation time of the DAR unit reaches 94 h and maintains an evaporator temperature between −9.5 °C and 3.5 °C. PV cells achieved an average daily efficiency of 12–13 %, with an overall system COP of approximately 0.055. These results demonstrate the system's capability to maintain effective cooling under varying solar conditions, making it suitable for remote areas without conventional electricity.